The beachflea Platorchestia platensis (Krøyer, 1845): a new addition to the Polish fauna (with a key to Baltic talitrid amphipods) - Urszula Janas; John I. Spice (Oceanologia, 2006)
The present paper reports for the first time on the occurrenceof Platorchestia platensis (Krøyer, 1845)(Crustacea, Amphipoda) in Puck Bay (southern Baltic, Poland)in May 2005. A key to the Baltic talitrids is given, which canbe used to identify males and females of the four species occurringon Polish shores (Talitrus saltator, Talorchestiadeshayesii, Orchestia cavimana, Platorchestia platensis) andadditionally Orchestia gammarellus, whichmay yet be found in the Polish coastal zone.